2015
DOI: 10.1093/bfgp/elv045
|View full text |Cite
|
Sign up to set email alerts
|

Building a KATalogue of acetyllysine targeting and function

Abstract: Acetylation is a dynamic post-translational modification that is attached to protein substrates by lysine acetyltransferases (KATs) and removed by lysine deacetylases (KDACs). While these enzymes are best characterized as histone modifiers and regulators of gene transcription, work in a number of systems highlights that acetylation is a pervasive modification and suggests a broad scope for KAT and KDAC functions in the cell. As we move beyond generating lists of acetylated proteins, the acetylation field is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…Since cells lacking HST3 and HST4 are reported to display increased sensitivity to DNA damaging agents (Celic et al 2006;Maas et al 2006), we reasoned that the positive effects of nicotinamide observed in our assays were likely due to inhibition of the remaining sirtuins, Hst1, Hst2, and Sir2, which impact the acetylation status of many proteins within the cell (Downey et al 2013(Downey et al , 2015Downey and Baetz 2016). However, an hst1D hst2D sir2D triple mutant failed to phenocopy treatment with nicotinamide ( Figure 1B).…”
Section: Nicotinamide Suppresses Mms Sensitivity Independently Of Sirmentioning
confidence: 94%
See 2 more Smart Citations
“…Since cells lacking HST3 and HST4 are reported to display increased sensitivity to DNA damaging agents (Celic et al 2006;Maas et al 2006), we reasoned that the positive effects of nicotinamide observed in our assays were likely due to inhibition of the remaining sirtuins, Hst1, Hst2, and Sir2, which impact the acetylation status of many proteins within the cell (Downey et al 2013(Downey et al , 2015Downey and Baetz 2016). However, an hst1D hst2D sir2D triple mutant failed to phenocopy treatment with nicotinamide ( Figure 1B).…”
Section: Nicotinamide Suppresses Mms Sensitivity Independently Of Sirmentioning
confidence: 94%
“…Despite their names, these enzymes also have nonhistone targets that play critical roles in maintaining cellular homeostasis in organisms from bacteria to humans (Choudhary et al 2009;Weinert et al 2011;Henriksen et al 2012;Choudhary et al 2014;Downey et al 2015). In S. cerevisiae, for example, acetylation sites have been mapped on over a third of all proteins (Downey and Baetz 2016 Maas et al 2006;Muñoz-Galván et al 2013;Che et al 2015;Simoneau et al 2015). Sir2, with the SIR silencing complex, is recruited to locations in the genome that have endured DSBs and is thought to promote DNA repair via the nonhomologous end-joining pathway (Martin et al 1999;Mills et al 1999;Tamburini and Tyler 2005) Although most Hst2 localizes to the cytoplasm, it enters the nucleus under some circumstances to interact with histones and regulate chromosome condensation, which is required for DNA segregation during cell division (Wilson et al 2006(Wilson et al , 2014.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the acetyltransferases and deacetylases that mediate this process are often mutated or aberrantly expressed in cancer, and histone deacetylase (HDAC) inhibitors have been widely used in cancer chemotherapy (Ma et al 2016). But whether histones themselves are the therapeutic targets of HDAC inhibitors is unclear, in that many nonhistone proteins, including metabolic enzymes, are regulated by acetylation (Downey and Baetz 2015). Furthermore, it has been proposed that a bulk function of histone tail acetylation is pH homeostasis, in which release of acetate and export from the cell reduces intracellular pH (McBrian et al 2013).…”
Section: Modifying Nucleosomesmentioning
confidence: 99%
“…The removal of these acetyl groups by enzymes called lysine deacetylases is also important (Downey and Baetz, 2015). …”
mentioning
confidence: 99%